Pengaruh Infrastruktur Dan Kondisi Sosial Ekonomi Terhadap Ketahanan Pangan - Adnan, Suraya; Surjono, Surjono; Sutikno, Fauzul Rizal (Fakultas Teknik, Universitas Brawijaya, 2014)
Food security can be affected by infrastructure and social economic condition. The purpose of this research is to analyze the effect of infrastructure and social-economic condition on rice price with path analysis. The second purpose of this research is to analyze the food purchasing power of people in Malang Regency as the indicator of food security. And then the third purpose is to analyze the effect of infrastructure and social-economic condition on food security based on exploratory data analysis (EDA). This research provides coefficient of the effect of infrastructure and social-economic condition on rice price, Y 1 = 2.917,99 + 0,54 X – 2,06 X 4 + 1,72 X , it means that rice price has a positive correlation with the price of substitutes goods, and road conditions. Rice price also has a negative correlation with the number of poor family, rice productivity, and width of road. The higher the price of some goods, the higher people’s expenditures, and finally people’s purchasing power become weaker. Generally, there is a correlation between infrastructure and social economic condition. This finding should encourage government to pay more attention to infrastructure and social sector in order to reach food security.Keywords: Infrastructure, Social-economic Condition, Food Security